The Nothingness of the Anguish in Søren Kierkegaard’s work as Modernity’s Infernal Redemption - Ormeny, Francisc-Norbert (Journal of Education Culture and Society, 2020)
The intention of this short study is to discuss the reverberations of Søren Kierkegaard’s philosophical considerations on anguish and on void in the context of the latest postmodern theoretical trends (Ben Woodard’s dark vitalism), by presenting the mechanisms by means of which the anguish gets to produce an “existential switch” which extracts the individual from the register of disintegration and introduces him into the register of the project (Heideggerianly speaking). I will try to demonstrate the compatibility between the structures of the late modernity and the Kierkegaardian vision on tension and on paradox, and will I will attempt to connect the possible findings to the relevant and congenial phenomenological, existentialist and aesthetic theories or set of theories circulating in today’s exegetical canon.